Effects of different litters on ammonia emissions from chicken manure - Tan, Hequn; Li, Meng; Jie, Dengfei; Zhou, Yafang; Li, Xin'an (International Journal of Agricultural and Biological Engineering, 2019)
Experiments were conducted to investigate the influences of type of litter, initial moisture content (IMC) of litter, and dry weight ratio of manure to litter (DWRML) on ammonia emissions from chicken manure and the effects of pH values of tea leaves and the mixtures of tea leaves and other litter on the ammonia emissions from chicken manure. For the experiments, four kinds of litter, Northeast pine sawdust (sawdust), rice husk, tea leaves, and wheat straw, were selected. The IMCs of the litter were (20±2)%, (30±2)%, and (40±2)%; and the DWRML values were 1:4, 1:6 and 1:8, respectively. The different litters adjusted at different moisture contents were mixed with chicken manure in different DWRML and then placed in different static test chambers, which were real-time monitored the ammonia concentrations. Pure chicken manure without any litter was used as a control group. The four kinds of litter had obvious inhibitory effects on the ammonia emissions from chicken manure under various conditions. There were significant differences among four kinds of litter (p < 0.01). Under the same conditions, the best inhibitory effect was achieved by using tea leaves, followed by straw, rice husk, and sawdust. The IMC of litter had no significant effects on the ammonia inhibition (p > 0.05). The DWRML had no significant effects on ammonia emission inhibition for tea leaves (p > 0.05), but had a significant effects on the ammonia emission inhibition for the other three kinds of litter (p < 0.05). The pH value of tea leaves had no significant effects on the inhibition of ammonia emissions (p > 0.05). The mixed litter made of tea leaves and sawdust, rice husk, or straw were significantly better than the tea leaves and other single litter (p < 0.01). It indicated that adding appropriate amount of tea leaves in the litter can effectively inhibit ammonia emissions from chicken manure.Keywords: litter, moisture content, dry weight ratio of manure to litter, chicken manure, inhibitory effect, ammonia emissionDOI: 10.25165/j.ijabe.20191204.5011Citation: Tan H Q, Li M, Jie D F, Zhou Y F, Li X A. Effects of different litters on ammonia emissions from chicken manure. Int J Agric & Biol Eng, 2019; 12(4): 27–33.